Myocardial fibrosis in rheumatic heart disease: emerging concepts and clinical implications - Putra, Teuku Muhammad Haykal; Rodriguez-Fernandez, Rodrigo; Widodo, Wishnu Aditya; Elfiana, Maria; Laksono, Sidhi; Nguyen, Quang Ngoc; Tan, Jack Wei Chieh; Narula, Jagat (Frontiers in Cardiovascular Medicine, 2023)
Rheumatic heart disease (RHD) remains a significant cardiovascular burden in the world even though it is no longer common in affluent countries. Centuries of history surrounding this disease provide us with a thorough understanding of its pathophysiology. Infections in the throat, skin, or mucosa are the gateway for Group A Streptococcus (GAS) to penetrate our immune system. A significant inflammatory response to the heart is caused by an immunologic cascade triggered by GAS antigen cross-reactivity. This exaggerated immune response is primarily responsible for cardiac dysfunction. Recurrent inflammatory processes damage all layers of the heart, including the endocardium, myocardium, and pericardium. A vicious immunological cycle involving inflammatory mediators, angiotensin II, and TGF-β promotes extracellular matrix remodeling, resulting in myocardial fibrosis. Myocardial fibrosis appears to be a prevalent occurrence in patients with RHD. The presence of myocardial fibrosis, which causes left ventricular dysfunction in RHD, might be utilized to determine options for treatment and might also be used to predict the outcome of interventions in patients with RHD. This emerging concept of myocardial fibrosis needs to be explored comprehensively in order to be optimally utilized in the treatment of RHD.